Transparent Ceramics: Scalable and Formable Tellurite‐Based Transparent Ceramics for Near Infrared Applications (Advanced Optical Materials 10/2016). Issue 10 (20th October 2016) - Bertrand, Anthony; Carreaud, Julie; Chenu, Sébastien; Allix, Mathieu; Véron, Emmanuel; Duclère, Jean‐René; Launay, Yann; Hayakawa, Tomokatsu; Genevois, Cécile; Brisset, François; Célarié, Fabrice; Thomas, Philippe; et al.
Abstract : Transparent tellurite polycrystalline ceramics are demonstrated to be simply elaborated by full and congruent crystallization of the 75TeO2 ‐12.5Bi2 O3 ‐12.5Nb2 O5 parent glass, by G. Delaizir and co‐workers on page 1482. The low‐temperature tellurite glass elaboration and its stability both enable the preparation of scalable tailor‐shaped ceramics with high refractive index, transmission in the near infrared range up to 5.5 μm, and promising mechanical/thermal properties.